Corporate Environmental Responsibility In India: Legal Accountability And Managerial Challenges In ESG Compliance (International Journal of Environmental Sciences, 2025)
With the increasing global shift toward sustainable development, the integration of Environmental, Social, and Governance (ESG) criteria into corporate strategy has emerged as both a legal requirement and a managerial imperative. This research explores the evolving legal framework governing ESG compliance in India, with a specific focus on corporate environmental responsibility (CER). The study analyzes key regulations such as SEBI’s Business Responsibility and Sustainability Reporting (BRSR), the Companies Act, 2013 (Section 135 – CSR), and relevant environmental statutes like the Environment Protection Act, 1986.The paper critically examines how Indian corporations are responding to mandatory ESG disclosures, the effectiveness of environmental audits, and the role of board-level oversight in ensuring compliance. Using a mixed-methods approach—comprising case studies of listed Indian firms, semi-structured interviews with compliance officers, and legal document analysis—the research highlights systemic gaps in enforcement, greenwashing concerns, and the operational challenges faced by management in aligning with environmental law mandates.The study concludes with a policy roadmap for improving legal accountability mechanisms and proposes a model ESG governance structure for corporations operating in environmentally sensitive sectors.